Qualidade e alterações estruturais do café arábica submetido a alternância da temperatura na secagem - Oliveira, Pedro Damasceno de [UNESP] (2015)
The objective of the present work to evaluate, at the end of the drying process with alternating temperatures, sensory quality, physico-chemical and physiological of processed coffee beans, dried and stored in time twelve months. The experiment was conducted with two types of processing: dry and wet; and seven drying methods: drying on ground and mechanical drying with air heated to 50°C until the coffee reaches 30% water content, continuing to the drying air heated to 35°C up to 11% water content; drying fixed bed heated air dryers at 45°C until the coffee reaches 30% water content, continuing to the drying air heated to 35°C until 11% water content; and drying in fixed bed dryer with air heated to 40°C until the coffee reaches 30% water content, continuing to the drying air heated to 35°C until 11% water content; Drying in fixed bed dryer with air heated to 35°C until the coffee reaches 30% water content, continuing to the drying air heated to 50°C until 11% water content; Drying in fixed bed dryer with air heated to 35°C until the coffee reaches 30% water content, continuing to the drying air heated to 45°C until 11% water content; Drying in fixed bed dryer with air heated to 35°C until the coffee reaches 30% water content, continuing to the drying air heated to 40°C until 11% water content. The mechanical drying system used consisted of three fixed bed dryers, which allowed the temperature control and drying stream. The storage area has not taken control of the atmosphere. After the treatments, the coffees were sampled according to the evaluation system proposed by the American Specialty Coffee Association (SCAA). In addition to the sensory analysis were made analyzes of physical and chemical composition, physiological quality and ultrastructural studies of coffee beans. The physico-chemical and physiological analyzes were: fatty ...